Engineering Cocatalysts onto Low‐Dimensional Photocatalysts for CO2 Reduction. Issue 10 (13th October 2021) - Di, Jun; Lin, Bo; Tang, Bijun; Guo, Shasha; Zhou, Jiadong; Liu, Zheng
Abstract : Cocatalysts Engineering for CO2 Reduction The CO2 reduction catalytic efficiency over low‐dimensional photocatalysts is limited by two factors, poor surface charge separation efficiency and lack of surface‐active sites. By engineering cocatalysts onto the low‐dimensional photocatalysts can ameliorate these issues. In article number 2100046 by Zheng Liu and co‐workers, the different strategies of engineering cocatalysts for performance optimization are summarized with the emphasis on structure‐performance correlations.